Maize grown in soil contaminated by mining tailings shows reduced growth and yield - Renata Maia; Yumi Oki; Milton Barbosa; Ricardo Luiz Louro Berbara; Geraldo Wilson Fernandes (Acta Scientiarum. Biological Sciences, 2025)
The 2015 Samarco dam collapse in Mariana, Brazil, resulted in the widespread deposition of mining tailings across agricultural lands in the Rio Doce Basin. This study was carried out in the municipality of Rio Casca, where a single maize variety was cultivated simultaneously in two comparable areas: one contaminated by mining tailings and one uncontaminated control area. Plants were of the same age and grown under similar climatic conditions, minimizing environmental variation. Soil and plant samples were analysed for physical and chemical properties, including nutrient and heavy metal content. The contaminated area showed reduced base saturation, lower effective cation exchange capacity, higher concentrations of Na, Fe, and Cu, and lower Mg concentration. Maize grown in contaminated soil exhibited reduced nitrogen balance index and chlorophyll content, thinner and broader leaves. Significant reductions in plant height, stem diameter, and overall biomass were also recorded for plants grown in the area exposed to mining tailings. Grain analysis further confirmed the negative effects of the mining tailings, with reductions in essential nutrients, like Ca, Mg, and N, and an increase in Na content, which can impair water uptake and cause ion toxicity. These findings show that maize grown in soil contaminated by mining tailings accumulates nutrients differently in leaves, roots, and grains, and has lower chlorophyll content, growth, and yield. Despite identical fertilization and climatic conditions, the lower fertility and altered composition of the contaminated soil limited crop performance. These results underscore the lasting impact of tailings on soil function and maize productivity, reinforcing the need for targeted management in affected areas of the Rio Doce Basin.